Prevalence of Glucose-6-Phosphate Dehydrogenase Deficiency among hospitalized Children at tertiary care Hospital in Eastern Part of Nepal - Jha, Chandra Bhushan; Rimal, Hem Sagar; Subedi, Ram Bhakta; Parajuli, Surya Bahadur (Birat Journal of Health Sciences, 2022)
Introduction: Glucose 6 phosphate dehydrogenase deficiency is the most significant enzyme defect. It is X linked inherited disorder that affects males and females are rarely affected by lyonization. Severe jaundice, anemia and hemolytic crisis following ingestion of fava beans and certain drugs are known to occur in children with G6PD deficiency.  Therefore, routine neonatal and child screening programs to facilitate the identification and effective management of children with G6PD deficiency is paramount.Objective:  The main objective of this study is to find out the  hospital prevalence of G6PD deficiency in hospitalized children at Birat Medical College teaching Hospital.Methodology: This is a hospital based cross sectional study carried out in the Department of Paediatric, Birat Medical College Teaching Hospital  from30th  November 2020 to 30th May 2021. Three hundred children  upto to ten years of age admitted in department of  pediatrics were included in this study.  This study was performed on hospitalized children who were screened for G6PD deficiency. The test was carried out using the Randox G6PD quantitative in vitro test to determine the prevalence of G6PD deficiency among the admitted children upto 10 years of age.Data was analysed using SPSS version 16.Results:  This study was performed on 300 children, in which male babies (n=192; 64%) outnumbered the female babies (n=108; 36%). The majority of children were in the age group of < 1 years (n=131; 43.7%).The overall prevalence of G6PD deficiency was 9.3% of which 96.4% were moderately deficient while 3.6% was severely deficient.The highest proportion was noted in the age group of 1 to 5 years. The frequency of this disorder in males and females were 13.5% and 1.9% respectively which was statistically significant (p=0.001).Conclusion:  The present study confirms the high prevalence of G6PD deficiency in Eastern Region of Nepal. Therefore, we need to establish routine screening and educational programs in order to prevent grave complications in future.